A Comparison Between Injured and Uninjured Football Players on Selected Psychosocial Variables - Brewer, Britton W.; Petrie, Trent A. (My University, 1995)
The psychological impact of athletic injury on 916 NCAA Division I football players from 42 institutions was examined. The Center for Epidemiological Studies Depression Scale (CES-D) (Radloff, 1977), the Rosenberg Self-Esteem Scale (Rosenberg, 1965), and the Spielberger Trait Anxiety Inventory (Spielberger, Gorsuch, & Lushene, 1970) were used to assess depression, self-esteem, and trait anxiety, respectively. The Levenson (1974) Locus of Control Scales were used to measure perceptions of three dimensions of control (internal control, powerful others, and chance). Injured student-athletes reported significantly higher levels of depression and life stress than uninjured student-athletes. The findings, which were consistent with previous research, suggested that injury can be a significant stressor for student-athletes.
Keywords: depression; injury; stress